2013
DOI: 10.1126/science.1240248
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Inflammasome Activation by Intracellular LPS Independent of TLR4

Abstract: Gram-negative bacteria including Escherichia coli, Citrobacter rodentium, Salmonella typhimurium, and Shigella flexneri are sensed in an ill-defined manner by an intracellular inflammasome complex that activates caspase-11. We show that macrophages loaded with synthetic lipid A, E. coli lipopolysaccharide (LPS), or S. typhimurium LPS activate caspase-11 independently of the LPS receptor Toll-like receptor 4 (TLR4). Consistent with lipid A triggering the noncanonical inflammasome, LPS containing a divergent lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
1,317
4
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,322 publications
(1,386 citation statements)
references
References 36 publications
49
1,317
4
16
Order By: Relevance
“…In a TLR4-independent manner, endocytosed LPS activates caspase-11 and stimulates the production of IL-1b/IL-18 (Fig. 3) (Kayagaki et al 2013). In addition, another group has shown that cytosolic LPS activates caspase-11, resulting in endotoxic shock in mice (Hagar et al 2013).…”
Section: Caspase-11mentioning
confidence: 99%
“…In a TLR4-independent manner, endocytosed LPS activates caspase-11 and stimulates the production of IL-1b/IL-18 (Fig. 3) (Kayagaki et al 2013). In addition, another group has shown that cytosolic LPS activates caspase-11, resulting in endotoxic shock in mice (Hagar et al 2013).…”
Section: Caspase-11mentioning
confidence: 99%
“…Although seemingly intended as a mechanism to prevent infection of daughter cells from compromised haematopoietic progenitor cells, chronic pyroptosis resulted in cytopenia and immunosuppression [46,47]. Lastly, caspase-11-mediated pyroptosis may drive lethal endotoxemia by mediating the release of intracellular inflammatory mediators [17,18,48]. Collectively, such observations highlight the potential for pyroptosis to mediate pathology under certain conditions.…”
Section: The Dark Side Of Pyroptosis In Pathogen Clearancementioning
confidence: 96%
“…The inflammatory caspase sub-family is comprised of caspases-1, -4, -5, and -12 in humans and -1, -11, and -12 in mice. Caspase-11 has gained considerable attention in recent years, as it is activated upon intracellular delivery of bacterial lipopolysaccharide (LPS), and is implicated into endotoxemia [17,18]. Like caspase-1, active caspase-11 triggers pyroptosis.…”
Section: Pyroptosis Initiation By Other Inflammatory Caspasesmentioning
confidence: 99%
“…This noncanonical inflammasome induces GSDMD-mediated cell death and IL-1␣ secretion independently of caspase-1 in response to caspase-11-mediated sensing of cytosolic LPS (14,15,(19)(20)(21). Caspase-11-dependent cleavage of GSDMD and subsequent pore formation also triggers activation of the canonical NLRP3 inflammasome by inducing potassium efflux (22)(23)(24).…”
mentioning
confidence: 99%